Medication use and potential drug-drug interactions in a general surgery clinic: A descriptive studyMain points - Sevgi Teker Yıldırım; Şevket Cumhur Yeğen; Songül Tezcan (Heliyon)
Aim: Perioperative pharmacies optimize medication safety and patient-centered care during surgery. This research aims to assess medication usage and potential drug-drug interactions (pDDIs) in a general surgery clinic. Methods: This prospective and descriptive research was carried out in a general surgery clinic at a hospital in Turkey. The patients who were admitted for any surgical procedure and stayed for a minimum of 24 h were included in the study. Information on prior medication use as well as pre- and post-operative medications was documented. pDDIs were assessed using the Lexicomp database. Results: The study involved 95 patients, with a median age of 54 (ranging from 19 to 86). It was found that 66.3 % of the patients had at least one comorbidities. The average number of medications administered during the post-operative period was greater than during the preoperative period (5.7 vs 4.5, p < 0.0001). Furthermore, the incidence of pDDIs identified in doctors' orders after surgery was higher compared to before surgery (p < 0.05). Conclusion: In this study, the majority of patients scheduled for surgery had at least one comorbidity. We suspect that the elevated number of medications administered postoperatively could have led to pDDIs Consequently, we expect that clinical pharmacy services will help ensure the safe and rational use of medications in surgical clinics.